Two Theses of H.L.A. Hart about Responsibility and Punishment: 50 Years Later - Figueroa Rubio, Sebastián (2018)
In this paper we make a critical assessment of some claims made by H.L.A. Hart in his book Punishment and Responsibility. Particularly, two specific theses on responsibility and punishment are addressed: the primacy of liability thesis and the mixed character of the justification of punishment thesis. We introduce both theses and we analyze their explanatory potential through scrutiny of criticisms they have faced.